An improved nanosatellite attitude control simulator for experimental research - McCafferty-Leroux A; Newton A; Gadsden SA (SPIE, the international society for optics and photonics, 2023)
This paper details the design, fabrication, and development of an improved Nanosatellite Attitude Control Simulator (NACS). The NACS consists of a mock 1U CubeSat (MockSat), tabletop air-bearing, and automatic balancing system (ABS). The MockSat employs a reaction wheel array to exchange momentum with the rigidly-attached air bearing platform, and an inertial measurement unit to obtain orientation and angular velocity estimates. The ABS tunes the Simulator's center of gravity to coincide with the air bearing's center of rotation in an effort to minimize gravitational torques. This paper presents the majority of the mechanical design process, as well as future insights into the ABS control system. The NACS will be used to build numerous data sets for the development and training of new machine learning algorithms, as well as to benchmark, test, and compare different estimation and control strategies.
Keywords: 40 Engineering; 4010 Engineering Practice and Education; Bioengineering